Mortality and displaced mortality during heat waves in the Czech Republic - Kyselý, Jan (International journal of biometeorology, 2004)
The aims of this study were to assess impacts of hot summer periods on mortality in the Czech Republic and to quantify the size of the short-term displacement effect which resulted in lower than expected mortality after heat waves. The analysis covered the period 1982-2000 when several extraordinarily hot summers occurred in central Europe. Daily total all-cause mortality and mortality due to cardiovascular diseases (CVD) in the entire population of the Czech Republic (approximately 10 million inhabitants) were examined. The daily death counts were standardized to account for the long-term decline in mortality and the seasonal and weekly cycles. Heat-related mortality is better expressed if 1-day lag after temperature is considered compared to the unlagged relationship. With the 1-day lag, both excess total mortality and excess CVD mortality were positive during all 17 heat waves, and in 14 (12) heat waves the increase in total (CVD) mortality was statistically significant ( P=0.05). The mean relative rise in total mortality during heat waves was 13%. The response was greater in females than males and similar regardless of whether total or CVD mortality was used. The largest relative increases, exceeding 20% in both total and CVD mortality, were associated with heat waves which occurred in early summer (the first half of July 1984 and June 1994). The mortality displacement effect played an important role since mortality tended to be lower than expected after hot periods. The mean net mortality change due to heat waves was estimated to be about a 1% increase in the number of deaths. The large relative increases during some heat waves were particularly noteworthy since the study (in contrast to most analyses of the heat stress/mortality relationship) was not restricted to an urban area and/or an elderly population.
Keywords: senioři; Seasons; mortalita; Retrospective Studies; kojenec; mladiství; Česká republika; Middle Aged; vysoká teplota; mužské pohlaví; Infant; Adult; Czech Republic; dítě; Climate; Child; Cardiovascular Diseases; Child, Preschool; Infant, Newborn; ženské pohlaví; novorozenec; retrospektivní studie; předškolní dítě; Humans; Mortality; lidé středního věku; podnebí; Hot Temperature; rizikové faktory; dospělí; Female; Aged; Risk Factors; roční období; Adolescent; kardiovaskulární nemoci; lidé; Male